Environmental Management Cost and Business Sustainability of Oil and Gas Firms in Nigeria - Iyoha, Francis O.; Capntan, Philemon M.; Ekwe, Michael C.; Ogaba, Moses; Siliya, Queenta P.; Sumbane, Julai J. (International Journal of Economics and Financial Issues, 2025)
The mounting environmental crises caused by phenomena such as climate change, global warming, water and food shortages, energy consumption, biodiversity loss, environmental degradation, and agricultural vulnerability highlight the need for increased measures to safeguard the environment from the hands of world leaders. The goal of this article was to analyze the relationship between environmental management costs and the sustainability of listed oil and gas firms in Nigeria. Specifically, it employed the Global Reporting Initiative’s (GRI) sustainable environmental disclosure index as a measure of sustainability and environmental protection expenses, environmental remediation costs, and staff training costs as proxies for environmental costs. Using the ex-post facto research design, data was obtained from the chosen companies’ yearly financial statements covering the period from 2014 to 2023. We utilized E-views 9.0, a statistical tool, to execute three independent analyses on the data set: Pooled Regression, Random Effect Model, and Fixed Effect Model. The idea was to establish which model functioned best. The results of the Hausman test showed that the Fixed Effect Model was the best match for the given data. All three independent variables—“Environmental Protection Costs” (EPC), “Environmental Remediation Costs” (ERC), and “Staff Training Costs” (STC)—had considerable and favorable implications on the organizational sustainability index, according to the results. Therefore, the study reveals that oil and gas businesses in Nigeria may ensure more sustainable operations and a better environment by efficiently managing their environmental expenses. The report suggests that Nigerian oil and gas corporations should put more money into environmental protection, environmental studies, and worker training to keep their operations functioning smoothly and prevent having to pay to clean up pollution.